The Allowance for Uncollectible Accounts, Conservatism, and Earnings Management - JACKSON, SCOTT B.; LIU, XIAOTAO (KELVIN) (Journal of Accounting Research, 2010)
ABSTRACT We study the interrelation between conservatism and earnings management by examining the allowance for uncollectible accounts and its income statement counterpart, bad debt expense. We find that the allowance is conservative and that it has become more conservative over time. Conservatism may, however, facilitate earnings management. We find that firms manage bad debt expense downward (and even record income‐increasing bad debt expense) to meet or beat analysts’ earnings forecasts and that conservatism accentuates the extent to which firms manage bad debt expense. Further, we find that firms manage bad debt expense downward by drawing down previously recorded over‐accruals of bad debt expense that have accumulated on the balance sheet. An implication of our study is that tighter limits on the amount by which firms are permitted to understate net assets may reduce their ability to manage earnings.